Determinants of Audit Fees for U.S. Listed Companies 2007-2011 - Chen, Chen (2013)
This paper investigates the determinants of audit fees in the U.S. market from 2007 to 2010. The preliminary analysis applies the ordinary least square (OLS) regression on the panel sample data. Results reveal the auditee size, auditee complexity and auditee risk are the main determinants of audit fees. The non-audit service fees, changes of auditor also have impacts on audit fees. Besides, the audit fees are affected by whether the auditor is a big four auditor or not. There is a decrease trend on average of audit fees from 2007 to 2010. Subsequent analyses concentrate on the differences of the structure of audit price between different groups. The first investigation groups data by year to find the structural differences before and post financial crisis. The second one focuses on the differences between big four and non-big four auditors. Thirdly the data are grouped by company size to analyse the differences between large and small firms. Statistical differences are found in all three steps.